Atmospheric and oceanic conditions and the extremely low Bothnian Bay sea ice extent in 2014/2015. Issue 18 (18th September 2015) - Uotila, Petteri; Vihma, Timo; Haapala, Jari
Abstract The winter of 2014/2015 was the first for which we can be certain that the northernmost embayment of the Baltic Sea, the Bothnian Bay, remained partially ice‐free. We assess atmospheric and oceanic drivers responsible for this extreme event. In terms of atmospheric drivers, mild Bothnian Bay winters are characterized by positive North Atlantic Oscillation (NAO) associated with the advection of air from the North Atlantic. In winter 2014/2015, NAO was at a record high level and resulted in a northerly storm track associated with vigorous southwesterlies that drove ice toward the northeastern end of the bay. Furthermore, we found that the 1985–2015 Baltic Sea ice extent distribution differs from any other preceding 30 winter period since 1720 with a high confidence. Based on climate projections, it is very likely that in the next 50 years partially ice‐free Bothnian Bay will go from being an extremely rare event to a new normal.